What have economists been doing for the last 50 years? A text analysis of published academic research from 1960-2010 - Lea-Rachel Kosnik (Kiel Institute for the World Economy (IfW), 2015)
This paper presents the results of a text based exploratory study of over 20,000 academic articles published in seven top research journals from 1960-2010. The goal is to investigate the general research foci of economists over the last fifty years, how (if at all) they have changed over time, and what trends (if any) can be discerned from a broad body of the top academic research in the field. Of the 19 JEL-code based fields studied in the literature, most have retained a constant level of attention over the time period of this study, however, a notable exception is that of macroeconomics which has undergone a significantly diminishing level of research attention in the last couple of decades, across all the journals under study; at the same time, the "microfoundations" of macroeconomic papers appears to be increasing. Other results are also presented.
Keywords: A11; B4; 330; text analysis; economics research; research diversity; topic analysis